A study of effective elastic constants of glass-fibre reinforced thermoplastic pipes by theoretical method and simulation. (May 2019) - Zhang, Qian; Luo, Yun; Zhang, Yanting
Abstract: In this paper, a theoretical method, a 3D model and a simplified model are proposed to investigate the effective elastic constants of the glass-fibre reinforced thermoplastic (GFRT) pipes. The effects of the layer thickness, winding angle and reinforced layer volume fractions of the GFRT pipes on the effective elastic constants are discussed. The results show that the proposed simplified model can predict the effective elastic constants in three directions very well. The effective elastic constants developed by theoretical method and simulation have a good agreement, and they are only related with the winding angle and the reinforced layer volume fractions. With the increase of the winding angle, E φ decreases, while E z and ν ρφ gradually increase. The pipes with winding angle of [ ± 45 ∘ ] give peaks of E ρ and G zφ . The ν zφ and ν zρ reach maximum and minimum values, respectively, when winding angle is [ ± 60 ∘ ] . There is a corresponding winding angle for optimal properties in different directions. Highlights: Effective elastic constants of GFRT pipes are studied by theoretical method. The results from theoretical method, 3D and simplified model agree well. Effective elastic constants are only related with the winding angle and the volume fractions. There is a corresponding winding angle for optimal properties in different directions.